Evidance Based Practice Penerapan Kompres Air Hangat untuk Menurunkan Demam dengan Diagnosa Demam Berdarah Dengue - Manampiring, Dio Juventa; Kairupan, Michelle Jessica; Lontoh, Esther (Yayasan Syalom Cipta Sumikolah, 2025)
The number of dengue fever (DHF) cases in North Sulawesi in 2021 was recorded at 1,196, with 32 deaths. Meanwhile, from January to June 2023, there were 1,120 cases of DHF in North Sulawesi. In Manado City, there were 230 cases of DHF in 2023. The purpose of this case study is to analyze the evidence-based practice of warm water compresses on An.E.M. to reduce fever. implementing interventions according to the EBN journal